The role of family functioning and socioeconomic context in multisite and chronic musculoskeletal pain in adolescents: Generation XXI Cohort study - Navasardyan, N.; Bernardes, S.; Henriques, A.; Oliveira-Gomes, C. F.; Pires, C.; Talih, M.; Lucas, R. (International Journal of Public Health, 2025)
Objective: We examined whether family functioning relates to multisite and chronic musculoskeletal pain in adolescents, a key etiological stage for chronic pain, considering socioeconomic and childhood adversity factors (ACEs). Methods: Data from 1,473 participants were analyzed using the Luebeck Pain Screening Questionnaire at 18 years. Multisite pain was defined as pain in ≥2 sites; chronic musculoskeletal pain as pain in any musculoskeletal site lasting >3 months. Family functioning was assessed via the Brief Family Relationship Scale and categorized as poor, fair, or good. Socioeconomic indicators were collected at baseline, and ACEs at age 13. Results: The prevalence of multisite pain was 43%, and chronic pain was 23%. Logistic regression analyses showed that good family functioning was associated with lower odds of multisite pain (OR 0.49; 95% CI 0.37, 0.65) and chronic musculoskeletal pain (OR 0.62; 95% CI 0.45, 0.86). Socioeconomic indicators had limited effects, though higher maternal occupation was linked to greater multisite pain (OR 1.38; 95% CI 1.02, 1.87). Stratified analyses revealed no significant interactions. Conclusion: Good family functioning was associated with a lower risk of adolescent pain across socioeconomic contexts.